KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA TANGAN MEDIUM SHOOT SISWA EKSTRAKULIKULER SMAN 3 KOTA PADANG - Pratama, Faisal; Frizki Amra; Sri Gusti Handayani; Indri wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue addressed in this study is the lack of accuracy in the medium-range shots of students participating in the basketball extracurricular program at SMAN 3 Padang. This inaccuracy is influenced by several dominant factors, such as leg muscle explosive power and hand-eye coordination. The study aims to determine the extent to which leg muscle explosive power and hand-eye coordination contribute to the medium-range shooting performance of these students. This is a correlational study. The population consisted of 40 students from the SMAN 3 Padang basketball extracurricular program, with a sample of 20 male students selected using purposive sampling. Instruments used included the vertical jump test for leg muscle explosive power, a basketball catch-and-throw test for coordination, and a specific medium-range shooting test. Hypothesis testing results indicate that: (1) leg muscle explosive power contributes 30.83% to the medium-range shooting performance; (2) hand-eye coordination contributes 49.97%; and (3) the combined contribution of leg muscle explosive power and hand-eye coordination is 53.32%.